Integrated marketing communication strategy using Quadruple Helix Approach to increase tourism visits to Mount Bromo - Lina Saptaria; Iin Kurniasari; Edwin Agus Buniarto; Iva Khoiril Mala; Ahmad Syamsudin (University of Merdeka Malang, 2024)
Integrated marketing communications is an important strategy in customer relationship management. In the context of digital marketing, Human Resources (HR) competency in management strategy will influence marketing performance. The decline in bookings for tour packages to Mount Bromo through Manjah Tour & Travel is due to the lack of effective communication strategies implemented. This community service activity (PKM) aims to implement IMC (Integrated Marketing Communication) with the QH (Quadruple Helix) approach as an effort to increase the number of bookings for tour packages to Mount Bromo. The method for implementing PKM (Community Service) activities is digital marketing training and assistance and increasing human resource capacity. The results of PKM activities show the achievement of optimizing the integrated use of Manjah Tour & Travel's website and social media. There was an increase in the number of tour package orders to Mount Bromo within 2 months after the implementation of the activity, where previously it was 4-6 packages to 15-20 packages per week. This training activity had an impact on increasing the strategic ability of partner management in implementing IMC with the QH approach, which previously had a value of 62 percent but then increased to 88 percent. This model can provide valuable insight in implementing IMC strategies in service businesses.